Design and Development of a Desktop-Based Library Information System for SMAN 1 Koto Salak: Rancang Bangun Sistem Informasi Perpustakaan SMAN 1 Koto Salak Berbasis Desktop - Puput Setia Utami; Evi Yulia Susanti; Elinda Revita (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2026)
School libraries play an important role in supporting the learning process by providing access to information resources for students and educators. However, library management at SMAN 1 Koto Salak is still conducted manually using ledger books, resulting in delays in data recording, inefficient borrowing and returning processes, and difficulties in generating reports. This study aims to design and develop a desktop-based Library Information System to improve the effectiveness and efficiency of library management. Data were collected through observation, interviews, documentation, and literature review, while the software was developed using the Waterfall model. The system was designed using the Unified Modeling Language (UML) and implemented using the Python programming language with MySQL as the database management system. System functionality was evaluated using Black Box Testing to ensure that all features operated according to user requirements. The results indicate that the developed system is capable of managing member data, book collections, borrowing and returning transactions, and report generation in an integrated manner. The implementation of the system improves the speed, accuracy, and efficiency of library management compared with the previous manual process.